COMMON COUPLED FIXED POINTS FOR TWO PAIRS OF w -COMPATIBLE MAPS IN PARTIAL G -METRIC SPACES - Rao, K. P. R.; Kishore, G. N. V.; Sadik, S. K. (Kathmandu University Journal of Science, Engineering and Technology, 2016)
In this paper we prove a unique common coupled fixed point theorem for two pairs of w-compatible mappings satisfying two contractive conditions in partial G-metric spaces. We also furnish an example to support our main theorem. Mathematics Subject Classification: 47H10, 54H25 Kathmandu University Journal of Science, Engineering and Technology Vol. 12, No. 2, 2016, page: 7-28